Sources and Helpfulness of Breastfeeding Information and Support Accessed by Australian Women Before and After Caesarean Birth - Sarah G. Abelha; Gloria Cheng; Jacki L. McEachran; Stuart A. Prosser; Diane L. Spatz; Donna T. Geddes; Sharon L. Perrella (Proceedings)
Caesarean section (CS) birth is associated with higher rates of breastfeeding difficulty and has an increasing prevalence in Australia and globally [...]